Figures 11 and 12 from Guo Xiang, et al. - Xiang, et al., Guo (International Journal of Agricultural and Biological Engineering, 2014)
Guo X, et al. Intelligent data acquisition and cloud services for apple orchard. Int J Agric & Biol Eng, 2014; 7(2): 146－153.